Securing healthcare data and optimizing digital marketing through machine learning: the CAML-EHDS framework - Abderrahmane, Fathi; Kawtar, Mouyassir; Waqas, Ali; Zahra, Fandi Fatima; Ali, Kartit (Institute of Advanced Engineering and Science, 2025)
Current healthcare data systems face major challenges in preventing unauthorized access, ensuring compliance with data privacy regulations, and enabling intelligent secondary use of patient information. To address these issues, we introduce cluster-based analysis with machine learning for enhanced healthcare data security (CAML-EHDS), a unified framework that combines homomorphic encryption, attribute-based elliptic curve cryptography (ECC), and semantic clustering with machine learning. CAML-EHDS improves upon existing models by offering fine-grained access control, adaptive threat detection, and data-driven insights while preserving privacy. Experimental results show that CAML-EHDS achieves up to 98% classification accuracy with low node count, and maintains 94% accuracy even at high node distribution levels, while ensuring encryption time under 24 seconds and acceptable data loss below 29%. Moreover, in comparative analysis with state-of-the-art models (support vector machine (SVM), random forest (RF), and decision tree (DT)), CAML-EHDS outperforms all in key metrics with an accuracy of 0.96. These results demonstrate CAML-EHDS’s potential for real-world deployment in secure, scalable, and intelligent healthcare environments, including privacy-aware digital marketing integration.